Bioavailability of the antiemetic metopimazine given as a microenema - HERRSTEDT, JØRN (1996)
The absorption of the antiemetic metopimazine (MPZ) given as a single dose of (a) 40 mg microenema, (b) 40 mg orally and (c) 10 mg as a 60 min i.v. continuous infusion was investigated in six healthy volunteers. Blood samples were drawn and the serum concentrations of MPZ and its acid metabolite were measured. The bioavailability of MPZ given orally and as enemas was 22.3 and 19.5% respectively. Partial avoidance of hepatic first pass metabolism was seen with the enemas, which in contrast to suppositories, seems to represent a reliable form of rectal administration.